The Use of Excel Statistics for Research Data Processing for Teachers of SMAN 3 Barru, Barru Regency, Indonesia: Penggunaan Statistika Excel Untuk Pengolahan Data Penelitian Bagi Guru SMAN 3 Barru Kabupaten Barru, Indonesia - R. Rusli; Abdul Rahman; Hamzah Upu; Ansari Saleh Ahmar; H. Hastuty (Mattawang: Jurnal Pengabdian Masyarakat, 2020)
This activity was carried out with the aim of: (1) Increasing teacher knowledge in processing and analyzing research data; (2) Developing teacher awareness and knowledge about the importance of data management in research data analysis; (3) Improving the insight, ability and skills of teachers in utilizing data to make it more informative by analyzing data using excel software; and (4) Reducing the number of teachers who perform data processing and analysis intuitively and manually in the computing era. The results of the implementation of this activity were: (1) The knowledge of teachers in processing and analyzing research data was increased; (2) The awareness and knowledge of teachers about the importance of processing and analyzing research data were developed; (3) The insight, ability and skills of teachers in utilizing data to be more informative with proper data processing and analysis were improved; and (4) The number of teachers who perform data processing and analysis intuitively and manually in the computing era was reduced. Abstrak Pengolahan data menggunakan Anaysis Toolspack dilakukan dalam bentuk pelatihan bagi guru-guru di Kab. Barru bekerjasama dengan UPT SMA Negeri 1 Barru Kabupaten Takalar. Pelatihan bertempat di SMA Negeri 1 Barru Kabupaten Barru dan dilaksanakan secara daring dengan menggunakan Zoom. Tujuan dari pelatihan ini adalah agar guru terampil dalam menggunakan paket statistik yang dimiliki Excel untuk mengolah data dan mengolah data menjadi satu informasi. Hasil pelatihan menunjukkan bahwa rata-rata kemampuan guru dalam menggunakan statistika pada paket excel analysis tools pack dalam mengolah dan mengolah data setelah pelatihan lebih baik (meningkatkan) daripada sebelum pelatihan.